Student Perception of a Visual Novel for Fostering Science Process Skills (Teaching and Learning Inquiry, 2022)
In undergraduate science education, emphasis is often placed on teaching subject matter rather than science process skills (e.g., critical thinking, problem solving). Although important to scientific training, these skills are often not taught because science educators do not feel equipped to teach them. We therefore present a case-scenario activity that aims to facilitate the development of science process skills. This activity, which takes the form of a visual novel, asks students to generate hypotheses for the seemingly odd events that are described in the story. We implemented this activity in a science-process-focused course. Upon completion of the activity, we asked students to submit a written response to the prompt: “What are you taking away from the activity?” In this exploratory study, we conducted a qualitative analysis of these written responses to ascertain whether meaningful codes and themes related to science process would arise from this open-ended prompt. Based on student responses, four main themes emerged: scientific inquiry, student satisfaction, flexibility, and collaboration. These results demonstrated the activity was both enjoyable, and it successfully enabled students to apply science process skills. We offer this activity in anticipation it will provide educators with a tool to include these skills in their classes.